2012
DOI: 10.5402/2012/947831
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of Blood Count and Tumor Markers in Patients with Borderline Ovarian Tumors: A Retrospective Analysis and Relation to Staging

Abstract: The aim of this paper was to evaluate the parameters of blood count and tumor markers in borderline ovarian tumors. We evaluated 21 patients who had confirmed histopathologic diagnosis of borderline ovarian tumor. We recorded age, parity, tumor type, stage of cancer, serum levels of tumor markers (CA-125, CA-15.3, CA-19.9, CEA, AFP), and the parameters of blood count, fasting glucose, disease-free survival and overall. The patients were divided into two groups, stage IA (n = 13) and stage IB-IIIC (n = 8). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Many studies examining tumor marker measurements in BOTs have reported low rates of abnormal CEA levels (8%-20%) (50-53) and concluded that CEA did not have any association with tumor presence (50). However, Nomelini et al, in their retrospective analysis of 21 patients, have noted that abnormal CEA levels were found more frequently in stages IB-IIIC, and suggested that this marker might have prognostic value in BOTs (54). Zhang et al evaluated 70 BOT patients, 60% of whom had abnormal CEA levels, and concluded that CEA can be effective in monitoring of BOT (55).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Many studies examining tumor marker measurements in BOTs have reported low rates of abnormal CEA levels (8%-20%) (50-53) and concluded that CEA did not have any association with tumor presence (50). However, Nomelini et al, in their retrospective analysis of 21 patients, have noted that abnormal CEA levels were found more frequently in stages IB-IIIC, and suggested that this marker might have prognostic value in BOTs (54). Zhang et al evaluated 70 BOT patients, 60% of whom had abnormal CEA levels, and concluded that CEA can be effective in monitoring of BOT (55).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Inflammatory factors may affect iron metabolism and inhibit erythropoietin expression and erythrocyte maturation. Haemoglobin level has been shown to be associated with prognosis in ovarian borderline tumours . In this study, IL‐6 levels were higher in patients with anaemia.…”
Section: Discussionmentioning
confidence: 49%
“…The final diagnosis may, nevertheless, be compounded by the fact that Echinococcusserology is false-negative in up to 25% cases of hydatidosis 16 and tumor markers may not be elevated in borderline ovarian tumors 17 as happened in this case.…”
Section: Discussionmentioning
confidence: 88%
“…However in addition to CA-125, CA 19-9 and CEA levels are also the part of the work up as CA-125 levels have be found to correlate more with advanced stage of borderline tumors and CA 19-9 and CEA levels are more frequently elevated in early stage disease. 17 Germ cell tumor markers like B-HCG and AFP should also have been part of workup as these tumors are more common in adolescents.…”
Section: Discussionmentioning
confidence: 99%